Chemical and process thermodynamics - Kyle, B. G. (Upper Saddle River, N.J. : Prentice Hall PTR, 1999)
The first chemical engineering thermodynamics text for the computer age, Chemical and Process Thermodynamics, Third Edition is an example-rich guide to chemical engineering thermodynamics that focuses on current techniques, new applications, and today's revolutionary computerized tools. You'll discover both the "how" and "why" of chemical engineering thermodynamics, and dramatically improve your problem-solving effectiveness with an extensive collection of sophisticated PC software.
In this book/CD-ROM package, the software isn't just a useful adjunct: its use is thoroughly integrated into the text and amply illustrated with worked examples.
System requirements for computer disk (programs by Y.L. Huang): IBM PC and compatibles; DOS; BASIC interpreter; floppy disk system; printer.
Keywords: Thermodynamics